Public Private Partnership (PPP) di Negara ASEAN: Analisis Bibliometrik Pembangunan Infrastruktur 2005–2025 - Reno Reno (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2026)
This study aims to analyze the development of Public Private Partnership (PPP) research in infrastructure development across ASEAN countries during the 2005–2025 period using a bibliometric approach. The research employs a descriptive quantitative method with bibliometric analysis techniques. Data were collected from Google Scholar and SINTA using Publish or Perish and visualized through VOSviewer. The results indicate a significant increase in PPP related publications after 2015, with major research themes focusing on policy, financing, risk management, and sustainability. Furthermore, the study finds that the gap between PPP literature and its implementation in ASEAN is not solely driven by institutional capacity and regulatory stability, but also by the dominance of research themes that tend to be normative rather than implementation oriented. The study also reveals a fragmentation of research focus across countries, where those with more stable regulatory frameworks demonstrate a deeper emphasis on implementation-related studies.